2015
DOI: 10.1371/journal.pone.0129007
|View full text |Cite
|
Sign up to set email alerts
|

Performance Comparison of Ultrasound-Based Methods to Assess Aortic Diameter and Stiffness in Normal and Aneurysmal Mice

Abstract: ObjectiveSeveral ultrasound-based methods are currently used to assess aortic diameter, circumferential strain and stiffness in mice, but none of them is flawless and a gold standard is lacking. We aimed to assess the validity and sensitivity of these methods in control animals and animals developing dissecting abdominal aortic aneurysm.Methods and ResultsWe first compared systolic and diastolic diameters as well as local circumferential strains obtained in 47 Angiotensin II-infused ApoE -/- mice with three di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 53 publications
1
23
0
Order By: Relevance
“…Trachet et al . have shown that in mice, determination of aortic stiffness using pulse wave velocity should be avoided and replaced by local stiffness methods 37 . Arterial distensibility was compared at equivalent blood pressure levels within the cardiac cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Trachet et al . have shown that in mice, determination of aortic stiffness using pulse wave velocity should be avoided and replaced by local stiffness methods 37 . Arterial distensibility was compared at equivalent blood pressure levels within the cardiac cycle.…”
Section: Discussionmentioning
confidence: 99%
“…LV dimensions were measured, and LV function was evaluated (Gao et al, 2011) using the equations in Table 1. Stiffness of the ascending aorta was assessed by its circumferential strain (Trachet et al, 2015), and cardiac output was estimated as the average of the aortic and pulmonary flow (Tournoux et al, 2011;Slama et al, 2015).…”
Section: Transthoracic Echocardiographymentioning
confidence: 99%
“…Because 1D and 2D ultrasound strongly depend on the field of view chosen by the user, 16 these findings indicate that for follow-up studies on aneurysm formation, 3D images should be acquired when possible. Both aortic regurgitation and ascending aortic volume were significantly increased after 10 days of angiotensin II infusion ( Figure 1G-1H).…”
Section: Trachet Et Al Ascending Aortic Aneurysm In Ang Ii-infused MImentioning
confidence: 99%